Association between subclinical mastitis pathogens and passive transfer of immunity in calves - Sanioglu Golen, Gokcenur (Frontiers in Veterinary Science, 2025)
IntroductionColostrum plays a critical role in providing passive immunity in newborn calves, and its immunological effectiveness is closely linked to the health status of the producing cow. Subclinical mastitis, an inflammation of the mammary gland without visible clinical signs, frequently caused by pathogens such as Staphylococcus aureus, Escherichia coli, Streptococcus agalactiae, and Corynebacterium bovis, can impair colostrum quality. Haptoglobin (Hp) and serum amyloid A (SAA) are acute phase proteins that increase during infection and inflammation and may serve as biomarkers for detecting subclinical mastitis and assessing its impact on calf health.MethodsColostrum and serum samples were collected from 20 healthy cows and 20 cows diagnosed with subclinical mastitis, along with their newborn calves. Bacteriological cultures were performed to identify mastitis pathogens. Hp, SAA, and total immunoglobulin (Ig) concentrations were measured using ELISA kits. Correlations between colostrum and calf serum biomarker levels were analyzed. Calves were monitored for diarrhea in the first week of life, and fecal samples from diarrheic calves were tested for common enteric pathogens.ResultsAll cows in the subclinical mastitis group were positive for at least one mastitis-causing pathogen, most frequently S. aureus (35%), followed by E. coli (30%), S. agalactiae (20%), and C. bovis (15%). Cows with subclinical mastitis had significantly higher Hp and SAA levels and lower Ig concentrations in colostrum compared with healthy cows (p < 0.05). Calves from the subclinical mastitis group also exhibited higher serum Hp and SAA concentrations and lower serum Ig levels (p < 0.05). Positive correlations were found between colostrum and calf serum Hp and SAA concentrations, while colostrum Ig showed negative correlations with both biomarkers. Four calves from the subclinical mastitis group developed diarrhea, all with low serum Ig concentrations, and fecal analysis revealed rotavirus, coronavirus, or E. coli K99.DiscussionSubclinical mastitis, particularly infections caused by S. aureus and E. coli, is associated with increased inflammatory markers and reduced immunoglobulin content in colostrum, leading to impaired passive immune transfer in calves. Elevated Hp and SAA in calves may indicate both passive transfer from colostrum and early activation of the neonatal immune system. These findings highlight the importance of pathogen-driven alterations in colostrum composition and support the potential of Hp and SAA as biomarkers for monitoring subclinical mastitis and predicting calf health outcomes.